Indigenous Territorial Autonomy and Self-Government in the Diverse Americas (University of Calgary Press, 2023)
Across the Americas, Indigenous and Afro-descendent peoples have demanded autonomy, self-determination, and self-governance. By exerting their collective rights, they have engaged with domestic and international standards on the rights of Indigenous Peoples, implemented full-fledged mechanisms for autonomous governance, and promoted political and constitutional reform aimed at expanding understandings of multicultural citizenship and the plurinational state. Yet these achievements come in conflict with national governments’ adoption of neoliberal economic and neo-extractive policies which advance their interests over those of Indigenous communities.